Unlocking Growth Opportunities for Philippine Micro, Small, and Medium Enterprises through Facebook Advertising and Growth Hacking Strategies in the Post-Pandemic Era - Guillen, Nelson; Lim, Cristina Teresa (Future Science / FSH-PH Publications, 2023)
The rapid digitalization and changing business landscape in the post-pandemic era have presented new growth opportunities and challenges for micro, small, and medium enterprises (MSMEs) in the Philippines. This study aims to explore the potential of Facebook advertising and Growth Hacking strategies as effective tools for unlocking growth opportunities for Philippine MSMEs during this transformative period. This study adopted survey research with 100 MSME owners and managers in Metro Manila, which investigated the current usage, perceptions, and effectiveness of Facebook advertising and growth hacking strategies. Additionally, it examined the factors influencing the adoption and implementation of these strategies, such as resource availability and digital literacy. The study’s findings intend to contribute to the understanding of how MSMEs in the Philippines can leverage Facebook Advertising and Growth Hacking strategies to drive business growth and navigate the evolving market dynamics in the post-pandemic era. The insights gained suggest practical implications for MSMEs, marketers, and policymakers, informing the development of tailored strategies and support mechanisms to utilize these digital tools for sustainable growth effectively.